2011
DOI: 10.5897/ajb10.1481
|View full text |Cite
|
Sign up to set email alerts
|

Induced spawning, fecundity, fertilization rate and hatching rate of Grass carp (Ctenopharyngodon idella) by using a single intramuscular injection of ovaprimC at a fish hatchery Faisalabad, Pakistan

Abstract: In the present study, intramuscular injection of ovaprim-C was studied on the number of eggs/kg, fertilization rate and hatching percentage during April to June 2008 at Fish Seed Hatchery, Satyana Road, Faisalabad, Pakistan on Grass carp (Ctenopharyngodon idella). Fishes were spawned successfully following a single dose of injection of ovaprim-C (luteinizing hormone releasing hormone analogue) with 0.6 ml/kg for female and 0.2 ml/kg for male. Ova and milt were stripped simultaneously and mixture was stirred fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…The Present study determined the time and temperature relationship for spawning and hatching of Hypophthalmichthys nobilis and Cyprinus carpio. Finding shows that Hypophthalmichthys nobilis spawned after the latency period of 8.80-10.84 hours of hormonal injection at 22-28 °C and have close resemblance with (Naeem et al, 2011). Cyprinus carpio showed spawning after latency period of 8.1-9.8 hours of hormonal injection at water temperature 22-28 °C.…”
Section: Degree-hours To Spawning Response Timementioning
confidence: 81%
See 1 more Smart Citation
“…The Present study determined the time and temperature relationship for spawning and hatching of Hypophthalmichthys nobilis and Cyprinus carpio. Finding shows that Hypophthalmichthys nobilis spawned after the latency period of 8.80-10.84 hours of hormonal injection at 22-28 °C and have close resemblance with (Naeem et al, 2011). Cyprinus carpio showed spawning after latency period of 8.1-9.8 hours of hormonal injection at water temperature 22-28 °C.…”
Section: Degree-hours To Spawning Response Timementioning
confidence: 81%
“…Cyprinus carpio showed spawning after latency period of 8.1-9.8 hours of hormonal injection at water temperature 22-28 °C. Spawning response time of Hypophthalmichthys molitrix after hormonal injection was reported in literature in 8-10 hours at 26-30°C (Ali et al, 2015) and in 9-10 hours at 24-28°C (Urooj et al, 2018) and in Cyprinus carpio showed spawning response time 8-12 hours at 24-27°C (Naeem et al, 2011).…”
Section: Degree-hours To Spawning Response Timementioning
confidence: 95%
“…After the first injection each two female breeders were transferred at once to a concrete spawning tank (9x4x1m) together with four uninjected males. As sex ratio of one female to two males was used in induced spawning for achievement of best results [21]. No anesthesia was given during transfer of brood fishes.…”
Section: Handling and Transfer Of Broodersmentioning
confidence: 99%
“…In the study by Rashid et al[36] the hatching rate for grass carp and silver carp was 70.10% and 69.71%, respectively and in the study carried out by Naeem et al[21] the hatching rate was 79.49%. In the experiment conducted by Singh et al[20] to test the efficacy of the technique of using dopamine antagonists with pituitary extracts on induced spawning of Indian major carps Cirrhinama mrigala, Catla catla, Labeo rohita, the hatching rate of fertilized eggs was 85.7% in the females treated with DOM and CPG together, while it was 72.7% in the females treated with CPG alone.The results of the present study compare well with those of commercial Linpe-based products such as ovaprim-c reported by Naeem, et al[21] on grass carp, which indicates an ovulation rate of 100%, a fertilization rate of 80.36%, and a relative fecundity of 62532 eggs/kg. Ovatide reported by Rashid et al[36] on grass carp and silver carp indicating that the ovulation rate was 100%, relative fecundity of grass carp and silver carp were recorded as 70000-80000 and 100000-110000 eggs/kg body wt.…”
mentioning
confidence: 98%
“…Then the eggs were discerned under a magnifying glass and fertilized eggs were counted with the assist of a soft thin brush. The fertilized eggs were easily disparate from the unfertilized eggs by the appearance of transparent shell with gray/ black spot within the eggshell, while the unfertilized eggs were non-transparent or opaque (Muhammad et al, 2011).…”
Section: Determination Of Fertilization Ratementioning
confidence: 99%